Relationship Between Self-Confidence and anxiety in Rehabilitants at the Tanah Merah Rehabilitation Center, East Kalimantan - Budiman, Arief; Afkarina, Izzeh; Fitri, Linda Dwi Novial; Pratiwi, Dwi (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Drugs stands for narcotics and illegal drugs. Which can reduce or change consciousness, reduce to eliminate pain, and can cause dependence. This study aims to analyze the relationship between self-confidence and anxiety in rehabilitants at the Tanah Merah rehabilitation center in East Kalimantan. Method: This study used a quantitative design method, the population in this study were 89 rehabilitants at the Tanah Merah rehabilitation center, East Kalimantan Badan Narkotika Nasional (BNN), the sampling technique used was total sampling, data analysis using the Chi Square test and the instruments used were the Self Confidence Scale questionnaire and the Hamilton Rating Scale for Anxiety. Result: The results of statistical tests regarding the relationship between self-confidence and anxiety obtained a value of P = 0.774 which is higher than the significant level of alpha 0.05, so it can be concluded that the hypothesis Ha is rejected and Ho is accepted. Conclusion: This study shows that the level of self-confidence does not significantly affect the level of anxiety in the population studied.